Calculating Radiation from Arbitrarily Shaped Aperture Antennas Using the Free Space Radiation Integrals - Booysen, Adriaan J. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A technique is derived by means of which the calculation of radiation from arbitrarily shaped aperture antennas can be greatly simplified compared to the conventional approach. In the conventional approach the null field region of an equivalence problem is typically filled with a conductor, effectively short-circuiting the aperture and the electric surface current density everywhere. The remaining aperture magnetic surface current density, which is known, then radiates in the presence of the conductor and the Green’s function associated with each particular antenna configuration has to be derived, usually a very cumbersome process. In the proposed technique a conductor is again placed within S, but with an infinitesimal small distance between the conductor and S. The image of the electric current density on S is shown to be induced on the conductor and the free space radiation integrals can now be used to solve the radiation problem. Examples are presented to prove the new technique and to demonstrate the mechanics of the equivalence principle when applied to aperture antenna problems.